Avaliação do grau de felicidade entre profissionais da área da saúde de um hospital geral de ensino - Barreiros, Ingrid Verônica Pinto (2016)
Happiness is desired and it s a goal and despite being subjective, it can be measured. Some researchers defined it as the way someone evaluates his life in a general manner besides his economic, health and social status. Nowadays there is a search for the best way to measure it. The first attempt had occurred at Far East, in Bhutan, during the 70 s. Today, UN (United Nations) has an index, the HPI (happy Planet Index) that can rank the countries according to the level of happiness and can be associated with GDP (gross domestic product) and HDI (human development index). In a small fashion, this concept is also utilized inside private organizations and there are apps for tablets and cells phones for this purpose. In this research, the authors evaluate the happiness perception level within two different groups of professionals, the first working at the administrative section and the second involving nurses. The two groups were composed by thirty subjects and work at a general educational hospital. For this purpose, they used the Oxford Happiness Report index with 29 items and the SF 36 report. By statistic analyses the authors correlated the different aspects of happiness within the two groups. Using social demographic questionnaire, the two groups were compared according to the happiness level and then with the SF 36 results. There were no significant differences between the two groups. The average happiness level were 4.70 for the administrative group and 4.52 for the nurse group. The Scale varies between 1, bad level of happiness until 6, excellent level of happiness